Comparison of Grain-Size Profile and Depositional Process in Mandeh and Nyalo Bar, Mandeh Bay, West Sumatera, Indonesia - Rahmadi Hidayat; Muhammad Fadli Rozamuri (Journal of Applied Geology, 2016)
Shipwreck of MV Boelongan Nederland situated in offshore of Mandeh Bay of West Sumatera is announced as potential area for tourism destination. Many studies were produced in term of its archeological and historical side but there is no significant work in sedimentological aspect. It is critical to understand depositional process of study area regarding the design of construction to minimize the impact of dynamic activity of waves within the area. Moreover, some areas along Mandeh Bay are covered by Cubadak Island as a protection for wave action derived from Indian Ocean that can produce more complexity in depositional process and will reflect to its characteristic of grain-size profiles. Utilizing thirteen sediment samples in two areas that correspond to inside (Mandeh Bar) and outside (Nyalo Bar) coverage of Cubadak Island, this study attempted to compare and contrast both grain-size profiles as well as interpretation of depositional process based on well-known analysis such as bivariate scatter plots, Linear Discriminant Function plot (LDF), Log probability curves and C-M diagram. Result of this study can be integrated by other researches to gain better policy in maintaining the shipwreck conservation. High energy of Indian Ocean wave supported by strong current clearly dominated depositional process in Nyalo Bar with coarser grain-size; good sortation, lower Y2 of LDF plot; extremely high population of traction materials and lower range of C-M. By contrast, presence of Cubadak Island disrupted the wave effectively and created lower and fluctuated energy in Mandeh Bar. This phenomenon was clearly depicted in its characteristic of finer grain-size with higher Y2 value; high abundance of saltation materials and greater ratio of C-M value.